Fertilizer consumption, pricing, and foodgrain production in Bangladesh - Hossain, Mahabub (International Food Policy Research Institute, 1987)
Rice and wheat occupy about 83 percent of the cropped area in Bangladesh, yet the country has to meet nearly one-tenth of its consumption of cereals through imports. It is well known that in Bangladesh, the potential for increasing food production through expansion of arable land is extremely limited, but the potential for substantially increasing crop yields is good. The. level of paddy yield is currently about 2.0 tons per hectare, which is one of the lowest in the world. 1 Even within the country, yields vary considerably. 2 Low yields result from the extensive use of traditional technology, relieved only by late and limited expansion in the use of modern inputs--high-yield variety seeds (HYVs), irrigation, and chemical fertilizers. Obviously any food production growth strategy in Bangladesh must focus on increasing the use of modern inputs and technology.